2007
DOI: 10.1016/j.juro.2007.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Results of Sacral Neuromodulation Therapy for Urinary Voiding Dysfunction: Outcomes of a Prospective, Worldwide Clinical Study

Abstract: This long-term study demonstrates that InterStim therapy is safe and effective for restoring voiding in appropriately selected cases refractory to other forms of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
331
8
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(384 citation statements)
references
References 17 publications
19
331
8
16
Order By: Relevance
“…This percentage is similar to other studies including other categories of patients suffering from non-obstructive chronic urinary retention. [12][13][14][15] However, the reasons for failure were identified in only two cases, and at this time we are only able to speculate on the unknown causes. Our findings showed that the time-duration of permanent SNM increased the possibility of failure, and the group of constant responders had a much shorter mean follow-up postpermanent SNM compared with the inconstant responder.…”
Section: Discussionmentioning
confidence: 80%
“…This percentage is similar to other studies including other categories of patients suffering from non-obstructive chronic urinary retention. [12][13][14][15] However, the reasons for failure were identified in only two cases, and at this time we are only able to speculate on the unknown causes. Our findings showed that the time-duration of permanent SNM increased the possibility of failure, and the group of constant responders had a much shorter mean follow-up postpermanent SNM compared with the inconstant responder.…”
Section: Discussionmentioning
confidence: 80%
“…[4][5][6][7][8][9] The mechanism of action is not entirely clear; however, inhibition of afferent signals presumably interrupts inappropriate detrusor contractions. 18,19 Although originally not thought to be a promising treatment option for patients with neurogenic bladder disorders, more recent studies suggest that these patients can benefit from SNM and up to 68% of patients in the test phase and 92% of patients in the permanent SNM phase can be successfully treated; 10,11 we report similar success rates (56.5 and 92.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…SNM has become a well-established treatment modality in recent years for patients with refractory non-obstructive chronic urinary retention, urgency-frequency syndrome and urgency incontinence. [4][5][6] Many patients have achieved significant improvement in lower urinary tract symptoms and bowel disorders, such as fecal incontinence and constipation. 5,[7][8][9] Originally, SNM was not considered as an option for neurogenic lower urinary tract dysfunction (LUTD); however, some studies now suggest that SNM is also effective in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The study groups comprised of 96 patients of both men and women and 60 female patients [36,37]. Significantly less incontinence episodes were found in 58 and 50% of the patients, respectively, and in 61 and 53% significant less use of pads.…”
Section: Oab With or Without Urinary Incontinencementioning
confidence: 99%